Transverse Initiation - Partom, Yehuda (European Journal of Applied Sciences, 2022)
The name transverse initiation was given to a situation where two explosives have a common interface, a detonation wave moves in the stronger explosive of the two perpendicular to that common interface, and the stronger explosive initiates the weaker explosive through the interface. In [1] they report on three configurations of transverse initiation tests, and on computer modeling of those tests. One feature of transverse initiation is the formation of an initiation layer in the weaker explosive along the common interface. Here we model those same tests using our reactive flow model TDRR (= reactant Temperature Dependent Reaction Rate). We get an initiation layer for the first two configurations but not for the third one. Also, there are some differences between our modeling results and those presented in [1], but there’s not enough information from the tests to conclude in favor of one of them.